PENGARUH KETAATAN ATURAN AKUNTANSI, WHISTLEBLOWING SYSTEM DAN MORALITAS INDIVIDU TERHADAP KECENDERUNGAN KECURANGAN (FRAUD) PENGELOLAAN KEUANGAN DESA DI KECAMATAN SERIRIT - Komang darma putra suryawan; Nyoman Ayu Wulan Trisnadewi (Vokasi : Jurnal Riset Akuntansi, 2025)
This research aims to examine the effect of compliance with accounting rules, the whistleblowing system, and individual morality on the tendency of fraud in village financial management in Seririt District. This research uses a quantitative method, with the population being the village government officials in Serint District. The research sample was obtained using a non-probability sampling method with a purposive sampling technique, with a total of 140 respondents. The method of data collection uses a questionnaire measured using a Likert scale. The data analysis technique used is multiple linear regression analysis. The research results show the following: (1) Compliance with accounting rules has a negative and significant effect on the tendency of fraud in village financial management in Seririt District, (2) The whistleblowing system has a negative and significant effect on the tendency of fraud in village financial management in Seririt District, (3) High individual morality can reduce fraud in village financial management in Seririt District, and (4) Compliance with accounting rules, the whistleblowing system, and individual morality have a significant effect on the tendency of fraud in village financial management in Seririt District.